2007
DOI: 10.1007/s00417-007-0559-8
|View full text |Cite
|
Sign up to set email alerts
|

Elevated vascular endothelial growth factor levels in Coats disease: rapid response to pegaptanib sodium

Abstract: Coats disease may have a component of dysregulation of VEGF-mediated angiogenesis as evidenced by elevated levels in this patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(57 citation statements)
references
References 5 publications
0
56
0
1
Order By: Relevance
“…1,5,6 Moreover, the elevated VEGF levels in the vitreous decreased markedly after the injection of an anti-VEGF agent. 1,5 Thus, the pathogenesis and progression of the disease are possibly regulated by VEGF secretion into the ocular fluid. Although anti-VEGF treatments may be a significant option for patients with Coats' disease, it is an enigma that immunolocalization of VEGF has yet to be elucidated in eyes with Coats' disease.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…1,5,6 Moreover, the elevated VEGF levels in the vitreous decreased markedly after the injection of an anti-VEGF agent. 1,5 Thus, the pathogenesis and progression of the disease are possibly regulated by VEGF secretion into the ocular fluid. Although anti-VEGF treatments may be a significant option for patients with Coats' disease, it is an enigma that immunolocalization of VEGF has yet to be elucidated in eyes with Coats' disease.…”
Section: Discussionmentioning
confidence: 99%
“…Together with a previous publication on VEGF, a major product of activated macrophages in the pathology of AMD, 10 these results suggest that macrophages play a critical role in the promotion of vascular permeability and angiogenesis by expressing VEGF in Coats' disease. Indeed, previous reports have demonstrated that the VEGF protein concentration was high in subretinal fluid in patients with Coats' disease, 1,5,6 correlated with the location of infiltrating macrophages and VEGF immunolocalization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sun et al [19] , reported of a 2-year-old boy with stage 4 Coats' disease, who had undergone an unsuccessful scleral buckle surgery with cryotherapy. A dramatic response was obtained after two intravitreal pegaptanib injections.…”
Section: A Review Of Intravitreal Treatment Alternatives Used As An Amentioning
confidence: 99%